Knowledge, attitude, and practice regarding organ donation among adult population of urban Puducherry, South India - Gokul Sarveswaran; Manikanda Nesan Sakthivel; Yuvaraj Krishnamoorthy; Yashodha Arivarasan; Jayalakshmy Ramakrishnan (Wolters Kluwer Medknow Publications, 2018)
BACKGROUND: India is currently having a deceased donation rate of 0.05-0.08 per million population. The National Organ and Tissue Transplant Programme have planned strategies to improve organ donation by creating awareness and capacity building. There is great need to assess the knowledge regarding organ donation among general population. OBJECTIVE (S): Among the adult population (≥18 years) residing in urban slum of Puducherry to determine the knowledge, attitude, and practice regarding organ donation. MATERIALS AND METHODS: Community-based cross-sectional study was conducted during April to May 2017 among 257 randomly selected participants in selected wards of urban Puducherry. Data regarding knowledge, attitude, and practice were collected through pretested semi-structured questionnaire. RESULTS: Mean (standard deviation) age of the study participants was 45 (15) years and majority (57%) were female, 41% of them were educated more than secondary. Almost 90% of the study participants have heard about organ donation. However, only 28% (95% confidence interval [CI]: 22.9-33.8) had adequate knowledge regarding organ donation. 58% (95% CI: 51.5-63.5) had positive attitude toward organ donation. Practice regarding registration for organ donation was only 2.3%. Knowledge regarding organ donation was more among joint family (odds ratio [OR] = 1.86, P = 0.02) and middle socioeconomic status (OR = 2.40, P = 0.01). Positive attitude was more among those who were educated above secondary (OR = 3.47, P = 0.001) and less among Muslim/Christian religion (OR = 0.49, P = 0.03). CONCLUSION: Less than one-third of the study population had adequate knowledge regarding organ donation. Even though more than half of them had positive attitude toward organ donation only six individuals registered for organ donation.